Clostridium Difficile (IntechOpen, 2023)
Clostridium difficile bacteria could be found everywhere around us: in the air, water, and soil and in the feces of humans and animals. You can easily become infected with C. difficile if you touch contaminated clothing, sheets, or other objects and then touch your mouth. Many people have the bacteria in their intestines and never have any symptoms. Still, it can cause symptoms ranging from diarrhea to life-threatening inflammation of the colon. The chance of developing a C. difficile infection increases with the usage of high doses of antibiotics over a prolonged period; thus, it is most often spread in the healthcare facilities between workers, patients, and residents. Each year in the United States, almost a half million people get sick from C. difficile, and approximately 29,000 patients died within 30 days of its initial diagnosis. Nowadays, C. difficile infections have become more frequent, severe, and difficult to treat. Therefore, the early diagnosis and the suitable treatment have become a real demand. In this book, we present the experience of worldwide specialists on the diagnosis and the treatment of C. difficile infections along with its lights and shadows.